BOOK REVIEW OF LOOKING FOR ALASKA WRITTEN BY JOHN GREEN - Hernowo, Kevin Bramantyo R. (LANTERN (Journal on English Language, Culture and Literature), 2016)
Main purpose of this review is to encourage readers to read Looking for Alaska and to understand the motive of the protagonist of this novel. This review contains some major spoilers from this novel. Looking for Alaska tells about changes and experiences which encountered by the protagonist while seeking his Great Perhaps. The novel also conveys what it means to love and to lose someone. After reading this review, the readers could understand this novel clearly and thoroughly.